Jerusalem: history of a global city - Lemire, Vincent; Berthelot, Katell; Loiseau, Julien; Potin, Yann; Froggatt, Juliana (University of California Press, 2022)
Introduction : spirits of places, fractures in time : toward a new history of Jerusalem -- The birth of a Holy City : 4000 BCE to second century CE -- Roman pantheon, Christian reliquary, and Jewish traditions : second to seventh centuries -- In the empire of the Caliphs : seventh to eleventh centuries -- Jerusalem, capital of the Frankish kingdom : 1099-1187 -- From Saladin to Süleyman : the Islamization of the Holy City, 1187-1566 -- The peace of the Ottomans : sixteenth to nineteenth centuries -- The impossible capital? : Jerusalem in the twentieth century -- Conclusion : the memory of the dead, the history of the living.